RESPONS PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS TANAMAN JAGUNG TERHADAP PEMBERIAN PUPUK N DAN K - Abdurrahman Abdurrahman Pandia1; Mbue Kata Bangun; Hasmawi Hasyim (Jurnal Agroekoteknologi, 2013)
The use of Central Composite Rotatable Design (CCRD) to determine the response surfaceyield at maize not yet a lot of checked, for that an research have been conducted in UPT BBITanjung Selamat, Regency of Deli Serdang, Province of North Sumatra with the land height ± 25 mabove sea level, at May 2012 - August 2012.The design was used is randomized block design withtwo factors, the first factor is two varieties (Bisma and SHS-4) and the second factor is fertilizerNK (the dose of NK determined from CCRD). Parameters measured were: plant height, the numberof leaf, the number of leaf above cob, the time of tasselling, the time of silking, the time ofharvesting, the rate seed filling, cob lenght, cob diameter, the number of lines per cob, the numberof seeds per cob, weight of 100 seeds and production of dry seeds. The results showed that thevarieties significantly on plant height, the number of leafs, the time of harvesting and dry seedsproduction. Fertilizer sigificantly on production of dry seeds. Interaction of varieties and fertilizerNK significantly on production of dry seeds.